Association of sex hormones with physical, laboratory, and imaging markers of anthropometry in men and women from the general population - Seyfart, Tom; Friedrich, Nele; Kische, Hanna; Bülow, Robin; Wallaschofski, Henri; Völzke, Henry; Nauck, Matthias; Keevil, Brian G.; Haring, Robin (PloS one, 2018)
The aim of this study was to evaluate the association of sex hormones with anthropometry in a large population-based cohort, with liquid chromatography-mass spectrometry (LCMS)-based sex hormone measurements and imaging markers. Cross-sectional data from 957 men and women from the population-based Study of Health in Pomerania (SHIP) were used. Associations of a comprehensive panel of LCMS-measured sex hormones with anthropometric parameters, laboratory, and imaging markers were analyzed in multivariable regression models for the full sample and stratified by sex. Sex hormone measures included total testosterone (TT), free testosterone (fT), estrone and estradiol, androstenedione (ASD), dehydroepiandrosterone sulfate (DHEAS), and sex hormone-binding globulin (SHBG). Domains of anthropometry included physical measures (body-mass-index (BMI), waist circumference, waist-to-height-ratio, waist-to-hip-ratio, and hip circumference), laboratory measures of adipokines (leptin and vaspin), and magnet resonance imaging-based measures (visceral and subcutaneous adipose tissue). In men, inverse associations between all considered anthropometric parameters with TT were found: BMI (β-coefficient, standard error (SE): -0.159, 0.037), waist-circumference (β-coefficient, SE: -0.892, 0.292), subcutaneous adipose tissue (β-coefficient, SE: -0.156, 0.023), and leptin (β-coefficient, SE: -0.046, 0.009). In women TT (β-coefficient, SE: 1.356, 0.615) and estrone (β-coefficient, SE: 0.014, 0.005) were positively associated with BMI. In analyses of variance, BMI and leptin were inversely associated with TT, ASD, and DHEAS in men, but positively associated with estrone. In women, BMI and leptin were positively associated with all sex hormones. The present population-based study confirmed and extended previously reported sex-specific associations between sex hormones and various anthropometric markers of overweight and obesity.